Koefisien Tanaman Padi Sawah pada Sistem Irigasi Hemat Air - Joko Sujono (agriTECH, 2011)
Traditional irrigation for paddy rice is the leading of consumer of water, about 80 % of the water resource availabilityused for irrigation purpose. This phenomenon is related to the way how to estimate the crop water requirement where crop coefficient for paddy rice (k ) (Prosida) is always greater than one starting from planting up to nearly harvesting. In this research, a number of water saving irrigations (WSI) systems for paddy rice cultivation using pots such asalternate wetting and drying (AWD), shallow water depth with wetting and drying (SWD), semi-dry cultivation (SDC), system of rice intensification (SRI), and  AWD with mulch (AWD-Mul) were applied. The amount of irrigated water and when it should be irrigated depend on evapotranspiration rate, soil moisture condition and the WSI system used. For this purpose, daily measurement of the pot weight was carried out. Crop coefficient (k )  is then caluculated as a cratio between crop and reference evapotranspiration computed using Penman-Montheit  method. Results show that up to 45 days after transplanting, the k of WSI treatments were around half of the k (Prosida) values currently used for computing the water requirement, whereas at the productive stage the k of WSI systems were relatively equal (AWD, SDC) to or greater (SRI, SWD) than the k (Prosida). Based on the the k values, the AWD and the SDC systems could save much water compared to the SRI or the SWD. Water saving could be increased by applying the AWD with mulch.ABSTRAKIrigasi padi sawah dengan sistem tradisional merupakan sistem irigasi  yang boros air, hampir 80 % sumber air yang ada untuk irigasi. Hal ini tidak terlepas dari perhitungan kebutuhan air tanaman dengan nilai koefisien tanaman (k) menurut Standar Perencanaan Irigasi (Prosida) selalu lebih besar dari satu mulai dari tanam hingga menjelang panen.Dalam penelitian ini beberapa metoda budidaya padi hemat air seperti alternate wetting and drying (AWD), shallow water depth with wetting and drying (SWD), semi-dry cultivation (SDC), AWD dengan mulsa (AWD-Mul) dan system of rice intensification (SRI)  diterapkan di lahan percobaan (pot). Jumlah dan kapan air irigasi harus diberikan tergantung pada besarnya laju penguapan, kelembaban tanah dan sistem irigasi hemat air yang digunakan. Untuk itu penimbangan pot dilakukan setiap hari sebelum dan sesudah pemberian air irigasi. Selanjutnya k dihitung berdasarkan ratio antara evapotranspirasi tanaman (aktual) dengan evapotranspirasi acuan yang dihitung dengan metoda Penman-Montheit berdasarkan data klimat yang tersedia.  Hasil penelitian menunjukkan bahwa pada awal tanam hingga fase pertumbuhan vegetatif (hingga 45 hari setelah tanam) koefisien tanaman k  sistem irigasi hemat air hampir setengahnya cdari nilai k (Prosida). Sebaliknya pada fase produktif nilai k metoda sistem irigasi hemat air hampir sama (AWD dan SDC) atau lebih besar (SRI, SWD) dari nilai k (Prosida). Berdasarkan nilai k , maka sistem pemberian air AWD dan SDC dapat menghemat air jauh lebih besar dibandingkan dengan metoda SRI dan SWD, penghematan air dapatditingkatkan apabila sistem AWD dikombinasikan dengan mulsa.